Effect of Work Motivation and Compensation on Employee Performance at PT. Vale Indonesia. Tbk. Luwu Timur – South Sulawesi - Ibriansyah Ibriansyah; Salju Salju; Sapar Sapar (Institute of Computer Science (IOCS), 2022)
The purpose of this study is that researchers want to know the effect of work motivation and compensation on employee performance at PT. Vale Indonesia Tbk. East Luwu-South Sulawesi. This research was conducted at PT. Vale Indonesia Tbk. East Luwu-South Sulawesi. The method used by researchers in this study using quantitative methods. The sample of this study was taken from employees of PT. Vale Indonesia Tbk. East Luwu-South Sulawesi as many as 286 employees obtained using the slovin formula. The data analysis used by the researcher is descriptive data analysis and multiple linear regression data analysis. Based on the calculation results, it is found that work motivation has a positive and significant effect on employee performance with a significant value of 0.000> 0.05 and is evidenced by the value of t count > t table , namely 15,658> 1,968. Likewise with the Compensation variable which has a positive and significant effect on Employee Performance with a significant value of 0.012 <0.05 and is evidenced by the value of t count > t table , namely 2.535> 1.968. Therefore, if work motivation and compensation are high, employee performance will increase.